History of Magnetism and Basic Concepts - Venkatesan, Munuswamy; Coey, John (Springer, Cham, 2021)
Magnetism is a microcosm of the history of science over more than two millennia. The magnet allows us to manipulate a force field which has catalyzed an understanding of the natural world that launched three revolutions. First came the harnessing of the directional nature of the magnetic force in the compass that led to the exploration of the planet in the fifteenth century. Second was the discovery of the relation between electricity and magnetism that sparked the electromagnetic revolution of the nineteenth century. Third is the big data revolution that is currently redefining human experience while radically transforming social interactions and redistributing knowledge and power. The emergence of magnetic science demanded imagination and observational acuity, which led to the theory of classical electrodynamics. The magnetic field is associated with electric currents and the angular momentum of charged particles in special materials. Our current understanding of the magnetism of electrons in solids is rooted in quantum mechanics and relativity. Yet only since about 1980 has fundamental theory underpinned rational design of new functional magnetic materials and the conception of new spin electronic devices that can be reproduced on ever smaller scales, leading most notably to the disruptive, 60-year exponential growth of magnetic information storage. The development of new magnetic concepts, coupled with novel materials, device and machine designs has become a rich source of technical innovation.
Handbook of Magnetism and Magnetic Materials
Keywords: Nanoscience & Materials; FABRICATION; NANOSTRUCTURES; Nanotechnology; Physics